Development of Triboelectric Devices for Human–Machine Interface Applications - Andreas Anastasopoulos; Vasiliki Zacharia; Achilleas Bardakas; Christos Tsamis (Proceedings)
Haptic feedback, also known as tactile sensing, plays a vital role in human interactions with the external environment. The artificial replication of tactile sensations using triboelectric sensors has sparked the attention of the scientific community by developing advanced electronic skins with haptic perception. In this work, we design and fabricate different flexible tactile sensors based on the triboelectric effect. The triboelectric sensors were evaluated in respect of their ability to identify different materials that were in contact with the sensor. Our results show that the triboelectric signal depends on the nature of the substrate, and a clear distinction among different substrates could be obtained.